“If Only It Makes Them Pretty”: Tattooing in “Prompted” Inuit Drawings - Jelinski, Jamie (Études Inuit Studies, 2018)
Tattooing was a widespread cultural practice amongst Inuit women for millennia before the first Europeans arrived in the Arctic. However, by the nineteenth century, colonial, imperial, and missionary mechanisms led to the decline of many pre-contact Inuit belief systems and practices, including tattooing. Although tattooing had begun to disappear from Inuit bodies by the late nineteenth century, it did not vanish altogether. Beginning in the early twentieth century, a number of Inuit, aided by newly introduced Western materials, transferred their knowledge of tattooing from skin to paper to create pictorial records of the pre-contact custom. This article begins by establishing an early precedent for post-contact Inuit drawing through the examination of work depicting tattooing collected by Reverend Edmund James Peck and Diamond Jenness. It then moves on to consider a group of twelve drawings collected by Danish-Inuk explorer and anthropologist Knud Rasmussen during the Fifth Thule Expedition. These drawings occupy a precarious place alongside other types of Inuit visual culture as they were originally collected as ethnographic artifacts, thus denying their aesthetic importance and interior Inuit cultural value. When reconsidered, these early drawings demonstrate the Inuit ability to appropriate Western materials as a form of both cultural endurance and record. Consequently, I argue that such drawings allowed tattooing to persist, albeit pictorially, despite the overall decline of the practice in its bodily form.